MEETING OF TWO THEOLOGIES IN INDIA IN THE 16th AND 17th CENTURIES - Mundadan, A Mathias (Journal of Dharma, 1989)
Most ancient Christian churches, whether they were of direct or indirect apostolic origin, had developed an individuality of their own. This individuality is seen in the worship form, church structure and discipline peculiar to them and, above all, in the theological and spiritual vision that emerged in each of these churches in course of time. We need not go in search the reasons for the growth of the individuality of each Church ; the individuality is a fact though individual characteristic liturgical, theological, spiritual, structural or disciplinary - and their expressions in each Church may vary in degree.